Efficient therapy of ischaemic lesions with VEGF121-fibrin in an animal model of systemic sclerosis. Issue 7 (11th September 2015) - Allipour Birgani, Shadab; Mailänder, Marion; Wasle, Ines; Dietrich, Hermann; Gruber, Johann; Distler, Oliver; Sgonc, Roswitha
Abstract : Background: In systemic sclerosis (SSc), chronic and uncontrolled overexpression of vascular endothelial growth factor (VEGF) results in chaotic vessels, and intractable fingertip ulcers. Vice versa, VEGF is a potent mediator of angiogenesis if temporally and spatially controlled. We have addressed this therapeutic dilemma in SSc by a novel approach using a VEGF121 variant that covalently binds to fibrin and gets released on demand by cellular enzymatic activity. Using University of California at Davis (UCD)-206 chickens, we tested the hypothesis that cell-demanded release of fibrin-bound VEGF121 leads to the formation of stable blood vessels, and clinical improvement of ischaemic lesions. Methods: Ninety-one early and late ischaemic comb and neck skin lesions of UCD-206 chickens were treated locally with VEGF121 -fibrin, fibrin alone, or left untreated. After 1 week of treatment the clinical outcome was assessed. Angiogenesis was studied by immunofluorescence staining of vascular markers quantitatively analysed using TissueQuest. Results: Overall, 79.3% of the lesions treated with VEGF121 -fibrin showed clinical improvement, whereas 71.0% of fibrin treated controls, and 93.1% of untreated lesions deteriorated. This was accompanied by significantly increased growth of stable microvessels, upregulation of the proangiogenic VEGFR-2 and its regulator TAL-1, and increase of endogenous endothelial VEGF expression. Conclusions: Our findings in the avian model of SSc suggest that cell-demanded release of VEGF121 from fibrin matrix induces controlled angiogenesis by differential regulation of VEGFR-1 and VEGFR-2 expression, shifting the balance towards the proangiogenic VEGFR-2. The study shows the potential of covalently conjugated VEGF-fibrin matrices for the therapy of ischaemic lesions such as fingertip ulcers.